Las 8 regiones geográficas del Perú - Torres Perez, Roifer (2018)
Nowadays, natural regions represent a problem; it is better to call them geographic regions; it is because in our means the natural regions have already disappeared. Around the world there is only one region the one which could be called in this way and it is the Antartida, because there are no many people there but especially the landscape is still natural. The varied geographical medium that we have in our country have motived through the time to make different essays and researches in the region, with different criteria and points of view. We are going to mention some classes. It is considered by some people as simple criteria, it comes from different Spanish conquers who in their chronicles inserted geographic descriptions and maybe the best one is the one of Pedro Cieza de Leon in his play “Crónica del Perú” (1533) stablishing for our country three well defined zones: the cost, sierra and jungle. Sierra is possibly the most important term in his play because it refers to the hilly relief and because of the presence of abundant hills (it has form of a saw when we observe from the horizon). A group of specialists prefer talk about bioregions. Ceballos, make a difference among regions, subregions, provinces, sub provinces, districts, areas, sub areas and three zones. Udvardi, recognize eight provinces bio regionals. The criteria of ecological floors has been created by Javier Pulgar Vidal, who mentions eight natural regions. Ecological floor is the geographical area with specific patrons and characteristics of an ecosystem and it makes different of an altitudinal floor tropical latitudinal.